Spatiotemporal Representations of Migrants from Big Cities to Saint Petersburg - SERGEYEVA, Valentina O.; NEYASKINA, Yulia Yu.; VODINCHAR, Ekaterina A.; FRIZEN, Marina A.; SHIRYAEVA, Olga S. (The journal of contemporary issues in business and government, 2021)
The integrity of space and time as a chronotope still needs to be researched both from the macro- and microchronotope point of view. The research of spatiotemporal representations of migrants from Russian cities includes three main aspects of migration to a metropolis: experience of living in the conditions of a city with a population of 100-250 thousand people, experience of living in the conditions of a metropolis, and migrant’s chronotope which synthesizes both in itself. It was established that the specifics of migrant’s chronotope as a special kind of microchronotope includes perception of time; a positive attitude towards both past and future time; perceiving new living environment; the attitude towards experience of belonging to the city.